Effectivity indicators in the German agriculture from the 1990s till today - Baráth, Lajos (Acta Agraria Debreceniensis, 2006)
Almost fifteen years have passed since the reunification of Germany. At the beginning of the 1990s, it was still unclear how the agricultural sector in the former East Germany would be able to survive, as it was still characterized by large scale farms, organized for a socialist economy. The course of this essay will look at how the agricultural productivity has changed the two different productivity systems in the western and eastern part of Germany. Productivity can be defined as output produced per unit of input. If we define productivity indicator as output per one type of inputs then we get so-called partial productivity index, however, if we define productivity indicator as output produced per unit of more than one inputs we get multi-factor productivity. In agriculture, the most often used partials productivity indexes are: labour, capital, land productivity and intermediate consumption productivity. The analysis of total factor productivity requires the aggregation of all inputs by using input prices.